Pengaruh Kurikulum Pengajaran Sekolah Minggu Berdasarkan II Timotius 3:15-17 Terhadap Minat Pelayanan Jemaat di Gereja Jakarta Baptist Citra Indah City Jonggol. - Banimata Josua; Arthur Sailendra; Ayu Sutrisna (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Effective church service is rooted in spiritual education from an early age, especially through Sunday School. II Timothy 3:15–17 emphasises the role of Scripture in shaping character and readiness for every good deed. This study aims to examine the effect of the Sunday School curriculum based on this verse on the interest of the congregation in serving the Jakarta Baptist Citra Indah City Jonggol Church. A theologically strong and pedagogically planned curriculum is believed to be able to transform the faith of children and teenagers into concrete actions in ministry. In Christian education, teaching is not only informative but also transformative, integrating faith and action. A Bible-based Sunday school curriculum can serve as a means of shaping character, faith, and awareness of a call to ministry from an early age. The interest in service itself is an internal drive that encourages a person's active involvement in service activities in response to God's calling. This study is expected to provide practical contributions to local churches in designing relevant and applicable spiritual curricula, as well as being able to foster a generation of ministers who are militant, loving, and ready to carry out their roles in the church and society.